FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN MELAKUKAN REVALUASI ASET TETAP SESUAI DENGAN PSAK 16 (2015) DI INDONESIA - Jannah, Raudhatul; Diantimala, Yossi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of study is to examine factors affecting the companys decision to revaluation of fixed assets in accordance with PSAK 16 (2015) in Indonesia. Independent variables used in this study is the leverage, liquidity, return on equity, investment opportunity set, a decline in operating cash flow, fixed assets intensity, and firm size. The population of this research is Non-Financial Companies listed on the Indonesia Stock Exchange in 2012-2015, using the method of purposive sampling. The data used in this research is secondary data in the form of financial statement. Data analysis was performed using logistic regression statistical analsys. Then data is processed by IBM SPSS 23th version program. The results showed leverage, liquidity, return on equity, investment opportunity set, a decline in operating cash flow, and firm size has no significant on the companys decision to revaluation of fixed assets, while fixed asset intensity has positively effect on the companys decision to revaluation of fixed assets.